1968
DOI: 10.3406/argil.1968.1088
|View full text |Cite
|
Sign up to set email alerts
|

Formation de beidellite par altération d'albite à l'autoclave à 200°. Etude en microscopie et diffraction électroniques

Abstract: L'albîte s'altère en kaolinite ou en beidellite en produisant d'abord, comme minéral intermédiaire, de la boehmite mal cristallisée. La transformation en kaolinite ne s'effectue que lorsque la solution est pauvre en silice et en ions sodium, La transformation en beidellite s'opère soit lorsque le rapport I a, croit dans la solution altérante, soit lorsque la concentration en silice dépasse celle d'une solution IH J saturee par de la silice cristallisée (ceci s'obtient par addition de silice amorphe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1990
1990
1995
1995

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…TEM confirmed that the flakes were composed of aggregates of thin fibers elongated in various direction and of bundles of fibers (not shown). Boehmites exhibiting similar habit have been reported by Tchoubar (1965) and . SEM of 5-day product showed that thin coating less than 0.1 pm thickness was precipitated on the obsidian surface on which very small spherical kaolinite less than 0.1 pm in diameter and flaky boehmite were likewise observed (Figure 2b).…”
Section: Products Of 200~c Experimentssupporting
confidence: 56%
“…TEM confirmed that the flakes were composed of aggregates of thin fibers elongated in various direction and of bundles of fibers (not shown). Boehmites exhibiting similar habit have been reported by Tchoubar (1965) and . SEM of 5-day product showed that thin coating less than 0.1 pm thickness was precipitated on the obsidian surface on which very small spherical kaolinite less than 0.1 pm in diameter and flaky boehmite were likewise observed (Figure 2b).…”
Section: Products Of 200~c Experimentssupporting
confidence: 56%
“…5A). Lath-shaped particles disposed at 60 ~ to each other, as observed by Tchoubar (1965), also occur ( Fig. 5B), but surface contaminating iron oxide particles (Jefferson et al, 1975) were not detected.…”
Section: X-ray Diffractionmentioning
confidence: 56%